Evidence for non-Dzyaloshinskii–Moriya ferromagnetism in epitaxial BiFeO₃ films - Prokhorov, V.G.; Kaminsky, G.G.; Kim, J.M.; Eom, T.W.; Park, J.S.; Lee, Y.P.; Svetchnikov, V.L.; Levtchenko, G.G.; Nikolaenko, Yu.M.; Khokhlov, V.A. (Физика низких температур, 2011)
BiFeO₃ films have been prepared by dc magnetron sputtering on LaAlO₃ (001) single-crystalline substrate. X-ray diffraction analysis and high-resolution electron-microscopy study reveal that the films have a highly coriented orthorhombic crystal structure. It was found that the magnetic properties of the BiFeO₃ films are typical for the ensemble of interacting superparamagnetic clusters rather than for the Dzyaloshinskii–Moriya weak ferromagnet. Appearance of the extrinsic nanoscale superparamagnetic clusters is explained by the oxygen deficiency in certain regions of the film, where the ferromagnetic ordering is realized through the double-exchange mechanism by Zener.